Work-Life Balance Among College Students Juggling Multiple Roles: A Phenomenological Study - Sindi Novitasari; Mochamad Widjanarko (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
The number of higher education students in Indonesia working full-time is rising, driven by pursuits of financial independence and career experience, yet balancing these dual roles often creates time management constraints that negatively affect academic performance and mental health. This study aims to explore and analyze in depth the dimensions of work-life balance (WLB) among working students using a qualitative method with a phenomenological approach. Informants comprised three unmarried, active undergraduate Psychology students (aged 22–25) in Kudus Regency who work full-time; data were collected through structured interviews, direct observation, and documentation, then analyzed using the constant comparative method covering data reduction, categorization, synthesis, and working hypothesis formulation, with credibility established through source triangulation. Findings show that under Work Interference with Personal Life (WIPL), informants reported chronic fatigue that reduced sleep, hobbies, and personal time, while under Personal Life Interference with Work (PLIW), toxic romantic conflicts and academic procrastination emerged as major distractions that lowered concentration and work productivity. Conversely, under Personal Life Enhancement of Work (PLEW) and Work Enhancement of Personal Life (WEPL), family support, salary appreciation, and peer flexibility served as positive coping mechanisms that restored emotional energy, boosted confidence, and sustained academic and professional motivation. Overall, working students' work-life balance is largely shaped by personal emotional regulation and the strength of their environmental support systems in managing dual-role pressures.